(untitled) (Research, Society and Development, 2022)
Objective: To assess the impact of oral lesions on quality of life factors, through the WHOQOL-bref questionnaire, and to perform a clinical analysis of oral involvement in lesions identified in patients with oral manifestations of dermatological diseases. Methodology: It is a pilot clinical study with a sample of convenience in which patients attended by the Oral Diagnosis sector who presented oral manifestations of pemphigus vulgaris (PV) and oral lichen planus (OLP), with histopathological diagnosis, were recruited. Results: Five foram patients treated with LPO and or PV, with four and one cases, respectively. All the patients foram mulheres de meia-idade. Two patients with OLP, who reported painful symptoms and, in their quality of life assessment, presented better average scores on general quality of life and general perception of health, in the environmental and psychological domains, when compared to those without painful symptoms. Conclusions: It is concluded that the assessment of quality of life through the WHOQOL-BREF questionnaire indicates that the psychological and environmental domains are the ones with the most diversity of scores, thus suggesting that these may have some association with oral lesions, especially symptomatic ones.